Healthcare communication barriers with amazigh immigrant - Ferrerós Pagès, Carla; Barrieras Angàs, Mònica; Roca Urgell, Francesc; Baltasar Bagué, Alícia (Revista Española de Comunicación en Salud, 2020)
Introduction: Study about communication problems taking into account issues related to the institution and to patients’ language and culture. The expression of symptoms related to non-organic issues will be studied from a linguistic point of view as it generates misunderstandings that may go unnoticed by professionals. Objectives: The main objective is to analyse the communication barriers with immigrant patients of Amazigh origin. Specific objectives: analyse the available resources and the training in relation to the care immigrant patients receive; detailing strictly linguistic difficulties. Methodology: Qualitative. Descriptive. Setting: Hospitals and primary health care centers in Girona and Barcelona areas have been chosen at random. Participants: 32 informants: 13 doctors, 9 nurses, 4 intercultural mediators and 6 social workers. Process followed: A survey and a partially structured interview. For the analysis of the conversations and the interpretation of their content Atlas.ti 6.0 software was employed. Results: The healthcare professionals detected an unequal distribution and a lack of resources and time. Possible communication difficulties go undetected in the majority of cases. Conclusions: Some linguistic aspects may make the communication between healthcare professionals and patients speaking different L1 difficult. More resources and training coming from healthcare institutions would help solve this problem.